The Australian System of Government - Fenna, Alan (Pearson Australia, 2013)
As noted in the opening chapter, Australia has a liberal-democratic system of government, incorporating, on the one side, the principle of majority rule and governmental accountability and, on the other, the principle of individual rights and the rule of law. As in all modern democracies, this is representative government, built around a set of political institutions through which citizens at large have some choice in who governs them. This chapter provides an overview of the way those institutions are structured and operate in Australia, highlighting seven key features: 1. Australian government is parliamentary government: voters do not elect 'the government' directly but elect a Member of Parliament, and the party that can muster a majority in the lower house of Parliament forms the government. 2. Australia has a federal system of government, comprising the Commonwealth government and the governments of the six original States. 3. Australian government is constitutional government, based on a combination of 'written' and 'unwritten' rules. 4. Australian government is characterised by strong bicameralism, with the Commonwealth Parliament and all but one of the State Parliaments being made up of two chambers, or 'houses', of essentially equal power. 5. Australia has retained colonial-monarchical heads of state, comprising the British monarch and what had originally been the monarch's colonial representatives, the State Governors, together with the Governor-General. 6. Australia has a system of judicial review whereby issues of constitutional law are settled by an independent supreme court (the High Court of Australia). 7. Unlike the United States and many other liberal democracies, Australia has not adopted a 'bill of rights' as part of its constitutional law.